Outcomes of pregnancy in maternal phenylketonuria (PKU): the north-east experience. (7th June 2011) - Jovanovic, A; Ferguson, C; Smith, M C; Leech, N; Waugh, J
Abstract : Background: Neonatal screening and early intervention for phenylketonuria (PKU) now results in normal development into adulthood for most patients. High maternal phenylalanine levels can be devastating for offspring with reports of 70% risk of microcephaly and 15% congenital heart defects in those with phenylalanine levels greater than 1000 µmol/l in pregnancy. The 2004 consensus for the diagnosis and management of PKU, recommends that women should aim for phenylalanine concentrations 60–250 µmol/l prepregnancy and throughout pregnancy. Methods: A retrospective audit of all pregnancies of mothers with PKU in a single regional clinic. Results: Between 2000 and 2009, The Newcastle PKU clinic had 42 females of reproductive age, of whom 16 conceived a total 20 pregnancies. Nine pregnancies resulted in normal healthy infants. One child has epilepsy. One congenital cataracts and one child was born with severe congenital cardiac abnormalities and died at 2 weeks. There were four early spontaneous abortions and four terminations of pregnancy. Preconceptual phenyalanine levels of <250 µmol/l were achieved in 8/20 pregnancies. All pregnancy resulting in spontaneous abortion or termination had phenylalanine >1000 µmol/l at presentation. Phenylalanine levels <300 µmol/l were achieved by 10 weeks gestation and maintained throughout pregnancy in 11/12 pregnancies that went to term, of which nine resulted in normal outcome. Conclusions: Despite counselling about the need for strict prepregnancy dietary control, most women conceived with above recommended phenylalanine levels. Intensive treatment to lower phenylalanine concentrations to target by 10 weeks, results in normal infants in most cases but PKU associated pregnancies remain high risk.